Epistemologiczne problemy badań interdyscyplinarnych - Angutek, Dorota (Studia Europaea Gnesnensia, 2013)
In the paper, the author summarizes two basic types of methodologies which are characteristic of the humanities, including social sciences, and sciences as such, i.e. anti-naturalism and naturalism. Then she goes on to compare their differences, pointing to the inability of arriving at a reconciled and uniform paradigm at a theoretical level. At the same time, Angutek argues that in various interdisciplinary projects the theoretical constraints are overlooked in practice, and the rapprochement of both branches is successfully pursued at the level of high technological and communicative efficiency. The discussed theoretical incompatibilities and the practical effective combination and application of knowledge from different fields are demonstrated on the examples taken from humanistic geography by Tommy Carlstein and Yi-Fu Tuan, as well as from Anthony Giddens’s sociological application of this geography. The author concludes that classical theoretical discourses are not relevant, while practical interdisciplinary projects overcome that gap, yielding new descriptive terminology.